Sol-gel template synthesis of mesoporous carbon-doped TiO2 with photocatalytic activity under visible light - Ovodok, Evgeni (2019)
Mesoporous TiO2 powders with an anatase framework were synthesized through surfactant-assisted template method. The concentrated titania sol (7-8 wt.%) prepared from TiCl4 as a precursor was used in this synthesis. The soluble triblock copolymer Pluronic F127 was employed as a structure-directing agent and a carbon precursor to fabricate the carbon-doped mesoporous titania. The synthesized powders were characterized by XRD, HRTEM, Raman spectroscopy, UV-Vis reflectance spectroscopy, N2 adsorption/desorption and TG/DSC methods. The mesoporous titania annealed at 350° C was shown to have a high specific surface area up to 192 m2/g and a narrow pore size distribution. After annealing, carbon species in graphitic form were detected in the template-prepared TiO2 samples using Raman spectroscopy measurements. The photocatalytic performance of the samples was characterized in the process of Rhodamine B decomposition under visible light irradiation. The enhanced visible light photocatalytic efficiency of the template-prepared TiO2 powders as compared with that of Degussa P25 can be attributed to the associated effects of high specific surface area, pure anatase crystalline structure and carbon doping.